Mathematical model of errors in measuring the interframe displacement of a measuring mark on an observation object using video from a WEB camera - O.Ye. Gorshenin; M.O. Gorshenin (Технічна інженерія)
This paper develops and analyses a mathematical error model for estimating the potential accuracy of measuring the inter‑frame displacement of a reference marker captured by a WEB camera. The case is considered when the WEB video camera is installed at a distance of about tens of centimeters from the measuring mark. The tag is the limb of the rotary mechanism of the ground antenna system of the X-band space radio link. Marker shift between consecutive video frames is calculated by locating the peak of the cross‑correlation function computed along corresponding image rows; this shift is then recalculated into antenna angle variation.